2017
DOI: 10.1021/acs.analchem.7b01816
|View full text |Cite
|
Sign up to set email alerts
|

High-Sensitivity Rheo-NMR Spectroscopy for Protein Studies

Abstract: Shear stress can induce structural deformation of proteins, which might result in aggregate formation. Rheo-NMR spectroscopy has the potential to monitor structural changes in proteins under shear stress at the atomic level; however, existing Rheo-NMR methodologies have insufficient sensitivity to probe protein structure and dynamics. Here we present a simple and versatile approach to Rheo-NMR, which maximizes sensitivity by using a spectrometer equipped with a cryogenic probe. As a result, the sensitivity of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
56
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 19 publications
(57 citation statements)
references
References 22 publications
1
56
0
Order By: Relevance
“…However, no NMR method that can supply this kind of physical stimulation had been established. Recently, we established high-sensitivity Rheo-NMR spectroscopy [ 10 ], which is a novel NMR methodology to analyze protein samples under shear flow in situ. Since shear flow accelerates the fibril formation of amyloidogenic proteins [ 6 , 7 ], the Rheo-NMR methodology enables us to observe the fibril formation of amyloidogenic proteins in situ at the atomic level.…”
Section: Introductionmentioning
confidence: 99%
“…However, no NMR method that can supply this kind of physical stimulation had been established. Recently, we established high-sensitivity Rheo-NMR spectroscopy [ 10 ], which is a novel NMR methodology to analyze protein samples under shear flow in situ. Since shear flow accelerates the fibril formation of amyloidogenic proteins [ 6 , 7 ], the Rheo-NMR methodology enables us to observe the fibril formation of amyloidogenic proteins in situ at the atomic level.…”
Section: Introductionmentioning
confidence: 99%
“…A Rheo-NMR apparatus was realized and a method for the measurement of the impact of applied flow rates was developed. In the first step, a Taylor-Couette geometry, which allowed the liquid fraction of n-hexadecane to be measured using a 400-MHz NMR spectrometer, was built and put into operation [20]. Pulsed-field gradient NMR also enabled the in-line and nondestructive determination of the droplet size distribution of the emulsion.…”
Section: Resultsmentioning
confidence: 99%
“…The fraction of crystallized particles was quantified by integration of the n-hexadecane peaks (CH 3 and CH 2 ). The Rheo-NMR measurement setup [20], temperature profile, and determination of solid fraction according to the NMR spectra can be found in the Supporting Information.…”
Section: Methodsmentioning
confidence: 99%
“…Because we previously observed the formation of β-sheet rich structures in M1-linked diubiquitin fibrils by circular dichroism [4], relatively flexible structures such as loops and edges of secondary elements might be converted into intra- or inter-molecular β-sheet structures in which these amide protons are more solvent-protected (Figure 4). Recently, we observed that the chemical shifts of the side chains of residues located in flexible regions (K11, P19, K48, Q62, and K63), the edges of the α-helix (E24 and K33), and the first 3 10 -helix (P37, P38, and D39) undergo changes during the formation of polyubiquitin fibrils from the native structure [20]. This suggests that inter-molecular associations and secondary structure changes in these regions take place in the course of fibril formation.…”
Section: Resultsmentioning
confidence: 99%